PECULIARITIES OF THE IMMUNE STATUS IN INDUSTRIAL WORKERS WITH PNEUMOCONIOSIS IN COMBINATION WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Rubtsov, R.V. (World of Medicine and Biology, 2020)
This article presents the results of the study on the status of humoral link in general immunity and functional activity of immune cells in workers of the mining and metallurgical industries with pneumoconiosis in combination with chronic obstructive pulmonary disease. It was found that in this category of patients humoral immunity indices were characterized by a significant increase in IgM (up to 4.5 g/l) and IgE (up to 465.6 IU/ml) compared with the control group, patients with pneumoconiosis and occupational chronic obstructive pulmonary disease. This indicated the formation of a pronounced "immune response" with the transformation of B-lymphocytes into plasma cells and stimulation of IgG secretion, promoting the prolongation of bronchopulmonary inflammation. Increased serum IgA (up to 2.8 g/l) is evidence of the simultaneous formation of “protective processes” in the respiratory tract. Reduction of spontaneous (up to 109.55 OU) and induced (up to 246.45 OU) activity of circulating immune complexes, as well as proliferative activity of lymphocytes (up to 1.29 OU) in the reaction of blast transformation of lymphocytes with mitogen coenzyme A increases the probability of recurrent disease. Increasing the content of complement (C3 component) to 1.24 g/l stimulates the production of histamine from mast cells and platelets that support phagocytosis, increase the permeability of vessel walls, spasm of smooth muscles, antigen-antibody reaction with the subsequent development of autoimmune processes in this category of patients.